Several Letters from Franciszek Zabłocki to Marcin Poczobut - Partyka, Magdalena (Senoji Lietuvos literatūra, 2021)
This article presents six previously unpublished letters from Franciszek Zabłocki to Marcin Poczobut written between 1789 and 1791 and found in the Wróblewski Library in Vilnius. Franciszek Zabłocki, better known as a poet and comedy writer, was also an official at the Commission of National Education. He wrote to Poczobut on various matters concerning schools and the situation of the academic community in the Grand Duchy of Lithuania, because Poczobut was the rector of the Principal School of the Grand Duchy of Lithuania and, under the Law of the Commission of National Education, managed schools and was obliged to report to the Commission on their work.
Keywords: Principal School of the Grand Duchy of Lithuania; Marcin Poczobut; Franciszek Zabłocki; Commission of National Education